Enseñanza de la filosofía en Colombia : hacia un enfoque multisensorial en el campo didáctico. (2013)
In this article we explore the effects of encryption educational practice philosophy. Then we link the teaching of philosophy with research on cognitive modifiability processes, which receive multisensory approaches to transform and make philosophy teachers acquire the ability to be critical subjectivities, to achieve this we present a proposal for teacher training pilot who current theories approaching neuroscience-intelligence. Teaching strategies are produced including multisensory visual thinking and as new educational alternatives.